2009
DOI: 10.1073/pnas.0813362106
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in expression of the human caspase-12 long variant determines susceptibility to Listeria monocytogenes infection

Abstract: Inflammatory caspases are important effectors of innate immunity.Caspase-12, of the inflammatory caspase subfamily, is expressed in all mammals tested to date, but has acquired deleterious mutation in humans. A single-nucleotide polymorphism introduces a premature stop codon in caspase-12 in the majority of the population. However, in 20% of African descendants, caspase-12 is expressed and sensitizes to infections and sepsis. Here, we examined the modalities by which human caspase-12 confers susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…Although more narrow in taxonomic scope than our study, Alexander's quantitative PCR study (Alexander et al, 2006) detected gender-specific differences in only two species of the altered Schaedler's flora (species of Firmicutes and Clostridium). Moreover, expression of a human caspase conferred differential susceptibility to Listeria monocytogenes infection in male and female transgenic mice, apparently due to estrogen interactions (Yeretssian et al, 2009). However, Kovacs et al (2011) found no gender differences in the CC mice of their study.…”
Section: Discussionmentioning
confidence: 86%
“…Although more narrow in taxonomic scope than our study, Alexander's quantitative PCR study (Alexander et al, 2006) detected gender-specific differences in only two species of the altered Schaedler's flora (species of Firmicutes and Clostridium). Moreover, expression of a human caspase conferred differential susceptibility to Listeria monocytogenes infection in male and female transgenic mice, apparently due to estrogen interactions (Yeretssian et al, 2009). However, Kovacs et al (2011) found no gender differences in the CC mice of their study.…”
Section: Discussionmentioning
confidence: 86%
“…Quantitative PCR (qPCR) was performed using iTaq SYBR Green Supermix (Bio-Rad, Philadelphia, PA) with primers as in Ref. 9. Fold induction was calculated over uninfected levels using the DD-Ct method.…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…They trigger inflammation by activating caspase-1, which cleaves pro-IL-1b and pro-IL-18 into their mature active forms. We have previously shown that a second member of the caspase-1 subfamily, caspase-12, which is catalytically inactive in humans and attenuated in rodents (6), acts as an inhibitor of both the inflammasome and NF-kB pathways (7)(8)(9). Expression of human caspase-12 is predominately confined to African descendents and is associated with dampened proinflammatory cytokine production and sepsisrelated mortality (8).…”
mentioning
confidence: 99%
“…25 Secondly, it has been suggested that females may have a more effective immune response than males as a result of estrogen-mediated inhibition of caspase-12 expression. 26 We suggest that both these mechanisms may be operational, protecting against infections and also contributing to women's better response to treatment through either improved cytotoxicity or enhanced immune function.It is of interest that female sex has emerged recently as a predictor of better outcomes not only in CLL but also, for example, in cutaneous head and neck melanoma. 27 Another recent report, in chronic myeloid leukemia, included female sex as one of the two more significant predictors of stable molecular response after long-term imatinib therapy.…”
mentioning
confidence: 99%
“…25 Secondly, it has been suggested that females may have a more effective immune response than males as a result of estrogen-mediated inhibition of caspase-12 expression. 26 We suggest that both these mechanisms may be operational, protecting against infections and also contributing to women's better response to treatment through either improved cytotoxicity or enhanced immune function.…”
mentioning
confidence: 99%